2015
DOI: 10.17221/8524-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of greying, melanoma, and vitiligo quantitative inheritance in Old Kladruber horses

Abstract: ABSTRACT:The paper deals with the greying process, melanoma, and vitiligo depigmentation occurrence in Old Kladruber horses (OKH). The study includes 376 animals of both sexes at the age of 1-25 years. The evaluation was performed repeatedly during 4 consecutive years. The greying status was measured spectrophotometrically on four body parts using L*a*b* colour system. Melanoma and vitiligo were detected visually and by palpation in all the animals and classified using 5 (3) grade scale. The GLM procedure of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 23 publications
(45 reference statements)
3
12
2
Order By: Relevance
“…As previously published [19,24], sex and the interactions of sex with age/ coat colour and geographical area were not significantly associated with melanoma (except the interaction sex and geographical area in S2). In the Camargue breed, a higher prevalence of melanoma was found in geldings compared with mares and stallions, but the differences were not statistically significant [21].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…As previously published [19,24], sex and the interactions of sex with age/ coat colour and geographical area were not significantly associated with melanoma (except the interaction sex and geographical area in S2). In the Camargue breed, a higher prevalence of melanoma was found in geldings compared with mares and stallions, but the differences were not statistically significant [21].…”
Section: Discussionsupporting
confidence: 68%
“…This is the first time that over 10,000 horses have been analysed. Despite the fact that heritability for the grey population was within the range of previous studies for MVS and MS outcomes [7,17,19], it was out of range for non-grey horses. This suggests the most severe forms of these diseases have less heritability, with an increased role of environmental effects, which is not the case in their most benign forms [17,22,26,27].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Therefore, an association between the coat colour paint and the presence of FFL cannot be confirmed from the results in the current study. It has been suggested that grey horses may be more prone to show FFL due to the higher risk of melanoma [19], which may cause defecation difficulties, but no such association has been identified in the literature or in this study. Social stress has been suggested to play a role for the presence of FFL, as the majority of FFL-affected horses did not defend their feed against other horses and were judged as low in the hierarchy in a previous study [1].…”
Section: Horsescontrasting
confidence: 64%
“…This breed, with unique characteristics and high cultural and historical value (Vostra-Vydrova et al 2016), is an important gene resource of the Czech Republic and the population has been fully closed since 2002 (Hofmanova et al 2015). Since the population of this gene resource breed is small, preservation of breeding material (i.e.…”
mentioning
confidence: 99%